Bio-Antifelting Treatment of Wool-Fiber Based on Ficin: Improvement and Effect on Dyeing with the Reseda luteola Plant. Issue 3 (May 2021) - Chemchame, Younes; Zahra, Mourid Fatim; Bouchti, Mehdi El; Kharchaf, Aboubakr
The objective of this study was to assess the effect of ficin enzyme as a new antifelting agent acting on wool yarn and fabric. The treatment effect on the dyeing efficiency of luteoline colorant that was extracted from weld ( Reseda luteola ) was also evaluated. The structural properties of antifelted and non-antifelted fibers were evaluated by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. An optimal enzymatic process for antifelting and shrink proofing was achieved at 40 °C for 3 h in alkaline medium at pH 10. The treatment increased the dye absorbance and fixation of luteoline colorant on the wool yarn and fabric. It also improved the fastness proprieties, particularly when a mixed mordant of natural alum and tannin from Acacia meransii were used.